Novel Program of Macrophage Gene Expression Induced by Phagocytosis of Leishmania chagasi - Rodriguez, Nilda E. (American Society for Microbiology, 2004)
Leishmania spp. are protozoans that survive and replicate intracellularly in mammalian macrophages. Antileishmanial immunity requires gamma interferon (IFN-γ)-mediated macrophage activation and generation of microbicidal effector molecules. The presence of intracellular Leishmania sp. impairs macrophage responses to IFN-γ, which has led to the description of macrophages as deactivated. It has recently become apparent that in addition to classical activation, macrophages can be activated by distinct triggers to express noninflammatory or anti-inflammatory genes. These nonclassical activation programs have been called alternative or type II pathways. We hypothesized that during initial contact with a phagocyte, leishmaniae activate one of these nonclassical pathways, resulting in expression of genes whose products suppress microbicidal responses. Using DNA microarrays, we studied gene expression in RNAs from BALB/c bone marrow macrophages with and without Leishmania chagasi infection. Some changes were verified by an RNase protection assay, reverse transcription-PCR, immunoblotting, or a bioassay. The pattern of genes activated by leishmania phagocytosis differed from the pattern of genes activated by bacteria or lipopolysaccharide and IFN-γ. Genes encoding some proinflammatory cytokines, receptors, and Th1-type immune response genes were down-modulated, and some genes associated with anti-inflammatory or Th2-like immune responses were up-regulated. Nonetheless, some markers of alternative (arginase) or type II activation (interleukin-10, tumor necrosis factor alpha) were unchanged. These data suggest that macrophages infected with L. chagasi exhibit a hybrid activation profile that is more characteristic of alternative or type II activation than of classical activation but does not strictly fall into either of these categories. We speculate that the pattern of genes upregulated by leishmania phagocytosis optimizes the chance of parasite survival in this hostile environment.